“Love for All” versus Religious Teachings: Attitudes towards LGBT among Heterosexual Malaysians - Yeoh, Jiin Yih; Ting, Su Hie; Jerome, Collin (Asian Scholars Network (002903215-H), 2021)
In Malaysia, LGBT is a punishable crime not only under the Syariah law but also under the civil laws. The present study examined how personal rationalisations mediate religious teachings on LGBT among heterosexual Malaysians, focusing in particular on their rationalisation for rejecting or accepting LGBT. Interviews were conducted with 12 participants from different religious backgrounds and the data were analysed thematically. The results of the study showed that a majority of Muslims and Christians rejected LGBT on religious grounds. The findings also revealed three rationalisations of Muslims and Christians rejecting LGBT. (1) LGBT goes against the teaching of God. It is viewed as a sin and this religious belief should be passed down to the next generation. (2) LGBT is morally wrong. (3) LGBT is physically wrong as they believe God creates male and female to produce offspring. Some participants acknowledged that Christians should be compassionate to LGBT individuals by giving moral support to them. However, one Buddhist participant rationalised the need to accept LGBT because of the core Buddhist teaching on love. The admonition of Buddha is not to harm others through sexuality. The study identified religious beliefs as one of the main influences people rejected LGBT culture but accepted LGBT individuals on the basis that they were human beings who deserved to be respected too.